Judicial verdict in the Romano-German legal system: analysis of procedural aspects (TSUL LEGAL REPORT, 2026)
This scientific article analyzes the procedural aspects of a court sentence within the framework of the Romano-Germanic legal system. The structure of the court sentence, its role in law enforcement, as well as its impact on judicial practice and society as a whole are considered. A comparative analysis of court sentences in the Romano-Germanic and general legal systems also highlights the features of this system.